From the Editor’s Desk - Alvita Nathaniel (Grounded Theory Review: An International Journal)
A few weeks ago, I received an email from a colleague who had submitted a paper to a highly regarded, high impact journal. The study was well designed and well described as a classic grounded theory. As often happens, a peer reviewer for the journal was not familiar with the tenets and procedures of classic grounded theory. Since research methods, procedures, and language vary among the varieties of classic and remodeled grounded theory methods are not interchangeable with those of classic grounded theory, the peer reviewer’s suggestion was inaccurate and inappropriate. Yet like many classic grounded theorists, the author needed to find a way to satisfy a reviewer who was unfamiliar with the specifics of the method. This is a tightrope that many classic grounded theorists walk— trying to appease poorly informed peer reviewers and journal editors while avoiding language that violates the major premises of classic grounded theory. This is never the case with The Grounded Theory Review.